Crystallization and preliminary X-ray diffraction analysis of prephenate dehydratase from Mycobacterium tuberculosis H37Rv - Vivan, A. L.; Dias, MVB; Schneider, C. Z.; de Azevedo, W. F.; Basso, L. A.; Santos, D. S. (Blackwell Publishing, 2006)
Tuberculosis remains the leading cause of mortality arising from a bacterial pathogen ( Mycobacterium tuberculosis). There is an urgent need for the development of new antimycobacterial agents. The aromatic amino-acid pathway is essential for the survival of this pathogen and represents a target for structure-based drug design. Accordingly, the M. tuberculosis prephenate dehydratase has been cloned, expressed, purified and crystallized by the hanging-drop vapour-diffusion method using PEG 400 as a precipitant. The crystal belongs to the orthorhombic space group I222 or I2(1)2(1)2(1), with unit-cell parameters a = 98.26, b = 133.22, c = 225.01 angstrom, and contains four molecules in the asymmetric unit. A complete data set was collected to 3.2 angstrom resolution using a synchrotron-radiation source.